Attitudes toward Hepatitis B Virus among Vietnamese, Chinese and Korean Americans in the Houston Area, Texas - Hwang, Jessica P. (J Community Health, 2012)
OBJECTIVES: We explored attitudes about prevention, screening and treatment of hepatitis B virus (HBV) infection in Chinese, Korean and Vietnamese communities. METHODS: We use qualitative methods in 12 focus groups (n=113) of adults who self-reported their ethnicity to be Chinese, Korean, or Vietnamese. We use grounded theory (i.e., consensus-building between co-coders about recurring, emerging themes) for analysis. RESULTS: Diet, nutrition, fatigue and stress were misidentified as HBV causes. Improving hygiene, diet, exercise, and holistic methods were misidentified as viable HBV prevention methods. Common screening problems included not affording test and not understanding test results. Participants shared reasons for using complementary and alternative medicine—when Western medicine fails or becomes unaffordable. Participants sought information from medical providers and fellow community members, but also from the internet. CONCLUSIONS: Many of the attitudes and opinions that emerged may deter participation in HBV screening, prevention and treatment, insofar as community members may factor them into healthcare decision-making, choose alternative but ineffective methods of prevention and treatment, and undervalue the benefits of screening. More patient education in both traditional and new media is necessary for clarifying transmission, screening and treatment misunderstandings.